COSMOLOGICAL AND EXPERIMENTAL CONSTRAINTS ON THE TAU-NEUTRINO - Sarkar, S; Cooper, A (1984)
Recent experimental results, together with a cosmological argument concerning the survival of primordially synthesized deuterium, exclude an unstable tau neutrino heavier than ≈ MeV. The cosmological bound on stable neutrinos then restricts it further to be lighter than ≈ 100 eV, in the absence of any available fast decay mode. These constraints are also relevant to other heavy neutrinos and unstable supersymmetric particles. © 1984.